2024
DOI: 10.1108/jfbm-11-2023-0282
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and socioemotional wealth as enablers of the impact of digital transformation in family firms

Virginia Lasio,
Juan M. Gómez,
John Rosso
et al.

Abstract: PurposeThe research aims to investigate how digital transformation (DT), entrepreneurial orientation (EO) and socioemotional wealth (SEW) impact the financial performance of family firms in uncertain business environments. Drawing from existing literature, we propose that DT and EO drive firm performance. Additionally, we suggest a new role for SEW, which positively moderates this relationship in family firms, especially in terms of risk behavior and innovation for survival.Design/methodology/approachWe used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…For instance, the digital transformation (DT) of family firms has emerged as a critical area where SEW plays a pivotal role. Recent studies have shown that entrepreneurial orientation (EO) significantly enhances the impact of DT on family firm performance, with SEW acting as a strategic asset that positively moderates this relationship [50]. This indicates that SEW can foster an environment conducive to technological adoption and innovative business practices.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the digital transformation (DT) of family firms has emerged as a critical area where SEW plays a pivotal role. Recent studies have shown that entrepreneurial orientation (EO) significantly enhances the impact of DT on family firm performance, with SEW acting as a strategic asset that positively moderates this relationship [50]. This indicates that SEW can foster an environment conducive to technological adoption and innovative business practices.…”
Section: Discussionmentioning
confidence: 99%